2020
DOI: 10.15407/agrisp7.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of brown trout (Salmo trutta), zebrafi sh (Danio rerio), and swan mussel (Anodonta cygnea) with infectious pancreatic necrosis virus (IPVN)

Abstract: Aim. Although more than 80 fi sh species and some invertebrate aquatic organisms are known to be susceptible to in- fectious pancreatic necrosis virus (IPNV) and aquatic birnaviruses, relatively little is known about its ability to infect brown trout (Salmo trutta), zebrafi sh (Danio rerio), and a mollusk, swan mussel (Anodonta cygnea). Therefore, the aim was to study in more detail the effects of IPNV on the said organisms. The information on the virulence of birnaviruses for aquatic organisms is important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(38 reference statements)
0
3
0
1
Order By: Relevance
“…IPNV (WB strain) was shown experimentally to be able to bioaccumulate in blue mussel (Mytilus edulis) and be transmitted to naive Atlantic salmon (Salmo salar) smolts (Molloy et al, 2013). Another experiment found that swan mussel (Anodonta cygnea) was resistant to IPNV, but able to accumulate and maintain substantial levels of the virus for 35 days (Rud et al, 2020). The following is a list of fish families where aquatic birnaviruses were isolated as a naturally occurring infection (McAllister, 2007) Parameter 6 -Domestic/farmed reservoir species (or family/orders) Farmed fish are an important reservoir of IPNV in aquatic environments, where the virus can be shed from farm waters into surroundings.…”
Section: Reservoir Animal Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…IPNV (WB strain) was shown experimentally to be able to bioaccumulate in blue mussel (Mytilus edulis) and be transmitted to naive Atlantic salmon (Salmo salar) smolts (Molloy et al, 2013). Another experiment found that swan mussel (Anodonta cygnea) was resistant to IPNV, but able to accumulate and maintain substantial levels of the virus for 35 days (Rud et al, 2020). The following is a list of fish families where aquatic birnaviruses were isolated as a naturally occurring infection (McAllister, 2007) Parameter 6 -Domestic/farmed reservoir species (or family/orders) Farmed fish are an important reservoir of IPNV in aquatic environments, where the virus can be shed from farm waters into surroundings.…”
Section: Reservoir Animal Speciesmentioning
confidence: 99%
“…IPNV (WB strain) was shown experimentally to be able to bioaccumulate in blue mussel ( Mytilus edulis ) and be transmitted to naive Atlantic salmon ( Salmo salar ) smolts (Molloy et al., 2013 ). Another experiment found that swan mussel ( Anodonta cygnea ) was resistant to IPNV, but able to accumulate and maintain substantial levels of the virus for 35 days (Rud et al., 2020 ). The following is a list of fish families where aquatic birnaviruses were isolated as a naturally occurring infection (McAllister, 2007 ), but it was not clarified in the publication if the virus described was IPNV: Acipenseridae , Amiidae , Anguillidae , Atherinidae , Bothidae , Carangidae , Catostomidae , Centrarchidae , Cichlidae , Channidae , Clupeidae , Cobitidae , Coregonidae , Cottidae , Cyprinidae , Cyprinodontidae , Embiotocidae , Esocidae , Gadidae , Gasterosteidae , Gobiidae , Hiodontidae , Ictaluridae , Lepisosteidae , Moronidae , Paralichthyidae , Percichthyidae , Percidae , Petromyzontidae , Pleuronectidae , Poeciliidae , Polyodontidae , Salmonidae , Sciaenidae , Soleidae , Thymallidae , Triglidae , Umbridae .…”
Section: Assessmentmentioning
confidence: 99%
“…to more than 700 million USD, and most likely every year financial investments in biotechnological developments of a preventive nature will grow in direct proportion to the intensive development of aquaculture [74,100,101].…”
Section: Antiviral Vaccines For Fish (A Review)mentioning
confidence: 99%
“…може становити понад 700 млн доларів США, і, найімовірніше, щороку фінансові інвестиції в біотехнологічні розробки профілактичного характеру зростатимуть прямопропорційно до інтенсивного розвитку аквакультури [74,100,101].…”
Section: Antiviral Vaccines For Fish (A Review)unclassified
“…В Україні захворювання інфекційний панкреатичний некроз зустрічається у палії (Salvelinus fontinalis), струмкової форелі (Salmo trutta) та райдужної форелі (Oncorhynchus mykiss) [2][3][4]. Через значний економічний вплив вірусу на галузь аквакультури, великі зусилля в усьому світі приділяють контролю захворювання за допомогою різних підходів: рання діагностика та оцінка біологічних ризиків, контроль торгівлі об'єктами аквакультури, скринінг природних популяцій та вивчення генотипів вірусу і розробка вакцин [1].…”
unclassified